Peran Hukum Admnistrasi Negara Dalam Penataan Pedagang Kaki Lima: Studi Kasus Di Kawasan Pasar Bambu Kuning Bandar Lampung - Sari, Nabila Permata; Khairudin, Khairudin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The regulation of street vendors (PKL) in the Bambu Kuning Market area of Bandar Lampung presents multidimensional challenges related to legal, social, and spatial planning aspects. This study aims to analyze the role of administrative law in the regulation process using a normative-empirical approach and case study method. The findings indicate that the implementation of PKL management policies remains weak in terms of legality, transparency, accountability, and public participation. The local government tends to adopt a repressive approach without valid administrative documentation and minimal involvement of PKL in policy formulation. Violations of key principles of administrative law, such as the principles of legality and proportionality, further exacerbate legal uncertainty and social inequality. This study recommends the reformulation of inclusive and responsive policies through the establishment of consultative forums and capacity-building for government officials in applying good governance principles and protecting citizens' rights in public space management